(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article, the author examines the questions of state-legal mechanism to ensure public access to environmental information. Protection of the environment, in turn, is a system of state and public measures aimed at preserving and restoring the environment, the prevention of the negative impact of economic and other activities on the environment and the elimination of its consequences. Key words: community, environment, information, law, law, government, environmental protection.